A SiO2 layer on PEO-treated Mg for enhanced corrosion resistance and bone regeneration - Qiu, Longhai; Zhang, Chi; Yang, Xiaoming; Peng, Feng; Huang, Yuliang; He, Yue (Frontiers in Bioengineering and Biotechnology, 2022)
Magnesium (Mg) is a promising biodegradable metal for orthopedic applications, and plasma electrolytic oxidation (PEO) has been widely studied as a corrosion protection coating on Mg-based implants. However, the porous structures and easily formed cracks in fluid are disadvantageous for long-term corrosion protection. In this study, a SiO2 layer was deposited on PEO-treated Mg to inhibit the formation of cracks on the PEO layer and prevent the permeation of corrosive fluid. The SiO2 layer did not alter the surface morphology of the PEO layer but considerably enhanced its corrosion resistance. The in vitro culture of MC3T3-E1 cells demonstrated the good cytocompatibility and osteogenic induction ability of SiO2-coated PEO-treated Mg, which could be attributed to Mg and Si ions released from the coating. The coating also favored the angiogenesis behaviors of HUVEC. Furthermore, with the continuous release of Mg and Si ions, the as-prepared implant showed a superior osseointegration ability in a rat bone implantation model. In summary, this newly designed Mg-based implant shows promising potential for orthopedic applications.